Extensive intraoperative peritoneal lavage (EIPL) for gastric cancer with positive peritoneal lavage and/or stamp cytology: An exploratory phase II study - Gen Tsujio; Masakazu Yashiro; Yuichiro Miki; Kohei Matsuoka; Koji Maruo; Mami Yoshii; Tatsuro Tamura; Katsunobu Sakurai; Takahiro Toyokawa; Naoshi Kubo; Shigeru Lee; Tomohisa Okuno; et al. (PLoS ONE, 2026)
Background Our group revealed that the combination of intra-operative stamp cytology and peritoneal lavage cytology (CY) improved the identification of individuals with high risk of peritoneal metastasis. In this exploratory Phase II study, we aimed to evaluate the effect on relapse-free survival (RFS) of extensive intraoperative peritoneal lavage (EIPL) for gastric cancer with positive peritoneal cytology (CY1) and/or stamp cytology positive (stamp+). Materials and methods This study was a single arm, multi-institutional, exploratory phase 2 trial to assess the effects of EIPL after open gastrectomy for gastric cancer with CY1 and/ or stamp+. The primary endpoint was RFS. Secondary endpoints were overall survival (OS), postoperative recurrence site and incidence of postoperative adverse events. Results Between 2017 and 2021, 13 patients from 2 institutions were enrolled in this study. Because of the recent decline in open abdominal surgery, the number of cases did not increase and the trial was closed due to lack of applicants at 13 cases. Median 3-year RFS was 14.5 months (95% CI 5.4-NA), median 3-year OS was not reached (95% CI 14.5-NA) and median3-year peritoneal RFS was 16.0 months (95% CI 5.4-NA). Median 3-year peritoneal RFS rate was 83% in CY0 and stamp+ cases (n=6), and 0% in CY1 and stamp+/- cases (n=7). (Log-rank p=0.015). Conclusion Because of the slow accrual pace and early stop of the trial, we were not able to evaluate the prespecified endpoints thoroughly. However, EIPL might be effective to prevent perineal recurrence, especially in CY0 and stamp+ case.